Special duty : a history of the Japanese intelligence community - Samuels, Richard J. (Ithaca : Cornell University Press, 2019)
"Two decades into the 21st century, after more than a century of dangerously uneven performance that contributed to national devastation and often uncomfortable subordination to their powerful U.S. ally, Japanese leaders have begun to reinvent their nation's flawed intelligence community"--
Driving intelligence -- Expanding special duties (1895-1945) -- Accommodating defeat (1945-1991) -- Tinkering with failure (1991-2001) -- Reimagining possibilities (2001-2013) -- Reengineering the intelligence community (2013- ) -- The past and future of Japanese intelligence.
First published 2019
Includes bibliographical references and index.
AAL
Keywords: Intelligence service -- Japan -- History